Crisis vs. Controversy. (28th January 2015) - Ziek, Paul
<x xml:space="preserve">Abstract</x> Communication is a response that can mitigate and even restore the damage resulting from organizational crisis. Yet what is often asserted in most of the research is that organizations are in a state of crisis and that they are indeed engaging in crisis communication. Sometimes organizations are in controversy as opposed to crisis. The distinction between controversy and crisis, in turn, has implications for the practice of communication. The current paper takes the opportunity to show the fruitful directions to be taken up based on the differences between crisis and controversy and how these differences impact organizational communication.